Answer:
6^-1
Step-by-step explanation:
6^-6 - (-5) = 6^(-6 + 5) = 6^(-1)
A lot of things are going on in this question. Notice how the 5 is handled. It starts off in the denominator as - 5 and when brought to the numerator it becomes -(-5) which makes it + 5.
The answer is then easy. It is 6^(-6 + 5) = 6^-1
You could give the answer as 1/6 but that is not what the question says.
Answer:
-5.02
Step-by-step explanation:
the result becomes negative because 7.273 is less than 12.37
Answer:
$93
Step-by-step explanation:
12(3.75+4.00)
= 93
Answer:
118 degrees
Step-by-step explanation:
A line has an angle of 180 degrees, so to find the unknown angle of b just subtract the known angle from 180.
180 - 62 = 118